Convergence in corporate governance: evidence from Europe and the challenge for economic geography. - Wójcik, D (Oxford University Press, 2006)
Using a dataset on corporate governance ratings of the 300 largest publicly traded European companies from 17 countries, I analyse the dynamics of corporate governance between 2000 and 2004 focusing on convergence. Within the structure of corporate governance, shareholders' rights and duties and takeover defences have changed little while ratings for board structure and functioning, and particularly for disclosure, have risen in every country and industry. Continental companies have narrowed the gap in relation to the UK and Ireland, and there is evidence of convergence within individual countries and industries. Nevertheless, the European corporate governance landscape is still diverse, with differences between countries overwhelming differences between industries.